Development of axisymmetric shell model for creep deformation analysis of reactor pressure vessel lower head - Jang Min Park; Kukhee Lim (Nuclear Engineering and Technology)
Under severe accident conditions of nuclear power plants, the lower head of a reactor pressure vessel can be at risk of creep deformation and potential failure. This study presents a computational model that can represent the creep deformation of the lower head through the application of shell theory. To account for the large deformation due to creep, kinematic equations are derived and implemented. Particularly, this study provides details of the mathematical formulation, which were lacking in previous studies. The analysis results using the developed model are compared with those of finite element analysis, considering deformation history, stress distribution, and deformed shape. A dimensionless time for the creep deformation is proposed based on the results, which can characterize the effective strain at failure. Finally, the developed model is applied to OECD lower head failure test for validation.